2008
DOI: 10.1136/jmg.2007.055806
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the clinical validity and clinical utility of DNA testing for hereditary haemochromatosis type 1 in at-risk populations

Abstract: DNA testing for hereditary haemochromatosis in at-risk populations has clinical validity and may have clinical utility. The review highlights the limitations of the literature and the methodological difficulties associated with evaluating this genetic test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Our model, consistent with other published studies, reported relatively high levels of uncertainty as evidenced by large standard deviations and 95% CIs reported in the base-case analyses [ 4 , 25 , 41 , 50 , 51 ]. However, these uncertainties were addressed in our one-way sensitivity analyses and, with the exception of discounting, were found to have little impact on the base-case results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our model, consistent with other published studies, reported relatively high levels of uncertainty as evidenced by large standard deviations and 95% CIs reported in the base-case analyses [ 4 , 25 , 41 , 50 , 51 ]. However, these uncertainties were addressed in our one-way sensitivity analyses and, with the exception of discounting, were found to have little impact on the base-case results.…”
Section: Discussionsupporting
confidence: 91%
“…The model incorporated four posterior probabilities in both the incidental and cascade screening sub-branches, specific to the tests ordered. The estimates of sensitivity and specificity for genotyping [ 41 ] and TfS tests [ 42 ] are displayed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review found sensitivity and specificity of C282Y homozygosity to be above 90% and almost 100%, respectively, for the presence of an iron overload phenotype in white northern Europeans. 19 A recent prospective population based cohort study showed that documented iron overload disease is rare among C282Y/H63D compound heterozygotes. 20 An advantage of genetic testing in patients with signs of increased iron stores is the certainty of the diagnosis, and this has important implications for treatment and counselling of first degree relatives.…”
Section: Genetic Testingmentioning
confidence: 99%
“…However, the review highlights the limitations of the literature and the methodological difficulties associated with evaluating this genetic test. 144 For Germany, a recent review discusses the cost effectiveness of different strategies of detecting patients via cascade screening, population screening, and genotyping. 145 It confirms the cost effectiveness of the current German policy to screen only for at-risk individuals, but suggests to conduct a DNA test after elevated iron levels have been found, instead of performing two transferrin saturation tests.…”
Section: Genetic Testing and Screening In Common Disordersmentioning
confidence: 99%